Understanding Attributions of Corporate Social Irresponsibility - Lange, Donald; Washburn, Nathan T. (Academy of Management Review, 2012)
Notwithstanding the significance to organizations of external reactions to bad behavior, the corporate social responsibility literature tends to focus on the meaning of and expectations for responsible behavior, rather than on the meaning of irresponsible behavior. Here we develop a theoretical perspective that explicitly focuses on irresponsibility and that particularly helps explain attributions of social irresponsibility in the minds of the firm's observers. In contrast to approaches in the corporate social responsibility literature that tend to deemphasize the role of the individual perceiver of firm behavior in favor of emphasizing such broader social structures as value systems, institutions, and stakeholder relations, our focus is on how the social reality of external expectations for social responsibility is rooted in the perceptions of the beholder. We draw on attribution theory to describe how attributions of irresponsibility stem from the observer's subjective assessments of effect undesirability, corporate culpability, and affected party noncomplicity. We describe how those assessments affect each other and how they are influenced by the observer's perceptions of effect and firm characteristics and by the observer's social identification with the affected party or the implicated corporation. We conclude by describing the important role of frames on irresponsibility attributions.